2020
DOI: 10.3390/membranes10090226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipid Environment in Ganglioside GM1-Induced Amyloid β Aggregation

Abstract: Ganglioside GM1 is the most common brain ganglioside enriched in plasma membrane regions known as lipid rafts or membrane microdomains. GM1 participates in many modulatory and communication functions associated with the development, differentiation, and protection of neuronal tissue. It has, however, been demonstrated that GM1 plays a negative role in the pathophysiology of Alzheimer’s disease (AD). The two features of AD are the formation of intracellular neurofibrillary bodies and the accumulation of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 182 publications
(317 reference statements)
2
26
0
Order By: Relevance
“… 48 A recent study by Vladimir Rudajev reported that sphingomyelin triggers oligomerization of Aβ40, which is one of the major biochemical hallmarks of Alzheimer’s disease. 49 In addition, previous lipidomics studies performed on the brains of wild-type mice at different ages revealed that the content of glucosylceramide, glucosylsphingosine, and GM1a was increased with aging. 50 In the present study, SM (d18:1/18:0) and glucosylceramide were significantly decreased after treatment with S. baicalensis compared with the normal cohort, and supporting evidence was also obtained for the serum levels of these lipids after treatment with Huang-Lian-Jie-Du-Tang.…”
Section: Discussionmentioning
confidence: 96%
“… 48 A recent study by Vladimir Rudajev reported that sphingomyelin triggers oligomerization of Aβ40, which is one of the major biochemical hallmarks of Alzheimer’s disease. 49 In addition, previous lipidomics studies performed on the brains of wild-type mice at different ages revealed that the content of glucosylceramide, glucosylsphingosine, and GM1a was increased with aging. 50 In the present study, SM (d18:1/18:0) and glucosylceramide were significantly decreased after treatment with S. baicalensis compared with the normal cohort, and supporting evidence was also obtained for the serum levels of these lipids after treatment with Huang-Lian-Jie-Du-Tang.…”
Section: Discussionmentioning
confidence: 96%
“…GM1 in lipid rafts mediate the pathophysiology of several cellular processes, including development, differentiation, and protection of neuronal tissue. GM1 has been proposed to play a negative role in Alzheimer’s disease by changing spatial organization of extracellular amyloid β [ 5 ].…”
Section: Lipid Raftsmentioning
confidence: 99%
“…It has been also reported that the lipid composition of membranes may modulate the cellular response to the toxic action of amyloid aggregates, thus explaining the different vulnerability of different cell types to amyloid species [ 95 ]. In particular, the importance of GM1, a major component of “lipid-rafts”, in the cellular membranes [ 96 ] as a mediator of amyloid toxicity has been widely documented [ 93 , 96 , 97 , 98 ].…”
Section: Functional Commonalitiesmentioning
confidence: 99%